2015
DOI: 10.3390/ijms161226147
|View full text |Cite
|
Sign up to set email alerts
|

Use of Inotropic Agents in Treatment of Systolic Heart Failure

Abstract: The most common use of inotropes is among hospitalized patients with acute decompensated heart failure, with reduced left ventricular ejection fraction and with signs of end-organ dysfunction in the setting of a low cardiac output. Inotropes can be used in patients with severe systolic heart failure awaiting heart transplant to maintain hemodynamic stability or as a bridge to decision. In cases where patients are unable to be weaned off inotropes, these agents can be used until a definite or escalated supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 43 publications
(49 reference statements)
1
80
1
1
Order By: Relevance
“…Moreover, in the Survival of Patients with Acute Heart Failure in Need of Intravenous Inotropic Support (SURVIVE) study including 1327 non‐PPCM patients, there was higher incidence of atrial fibrillation, hypokalemia, and headache without reduction of all‐cause mortality with levosimendan compared to dobutamine . The use of inotropic drugs in patients with CS is often limited due to the development of tachycardia, hypotension, and arrhythmias . In addition, these drugs should be used with caution during pregnancy as fetal safety is not known due to limited information …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the Survival of Patients with Acute Heart Failure in Need of Intravenous Inotropic Support (SURVIVE) study including 1327 non‐PPCM patients, there was higher incidence of atrial fibrillation, hypokalemia, and headache without reduction of all‐cause mortality with levosimendan compared to dobutamine . The use of inotropic drugs in patients with CS is often limited due to the development of tachycardia, hypotension, and arrhythmias . In addition, these drugs should be used with caution during pregnancy as fetal safety is not known due to limited information …”
Section: Discussionmentioning
confidence: 99%
“…21 The use of inotropic drugs in patients with CS is often limited due to the development of tachycardia, hypotension, and arrhythmias. 21,22 In addition, these drugs should be used with caution during pregnancy as fetal safety is not known due to limited information. 23 The recommendations of the PPCM working group for the management of severe PPCM also include considerations for the use of bromocriptine.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 However, most patients in these studies were not receiving β-blockers, which remains a lingering concern. 32 We have previously demonstrated that in 1842 propensity score-matched patients with HF (30% on β-blockers), a new digoxin prescription was associated with a lower risk of 30-day all-cause readmission (17% vs 22%; HR: 0.77, 95% CI:…”
Section: Digoxin Use and Long-term Outcomesmentioning
confidence: 99%
“…Whenever possible, nephrotoxic agents should be omitted in all pre‐HTx patients. When hospitalized, these patients are candidates for intravenous inotropic support to increase cardiac output and organ perfusion . The main principles of managing renal failure (either AKI or CKD) have been described before .…”
Section: Introductionmentioning
confidence: 99%